2015
DOI: 10.1130/b31230.1
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic evolution from subduction to arc-continent collision of the Junggar ocean: Constraints from U-Pb dating and Hf isotopes of detrital zircons from the North Tianshan belt, NW China

Abstract: The Junggar ocean, once situated north (present coordinate) of the Yili and Central Tianshan blocks during early Paleozoic to late Carboniferous time, was a major southern branch of the Paleo-Asian Ocean, the opening, expansion, and final closure of which led to the development of the Central Asian Orogenic Belt between Eastern Europe-Siberia and Tarim-North China. However, the detailed evolution of the Junggar ocean has not been well constrained. This paper reports U-Pb and Lu-Hf isotopic data of detrital zir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 89 publications
(160 reference statements)
2
64
0
Order By: Relevance
“…Ma adakites (zircon ε Hf (t) = -0.8~+2.7; Mao et al, 2010b) and 397 ± 3 Ma K-feldspar granite By contrast, Precambrian detrital zircons in this study correspond well with those previously reported Precambrian detrital zircons (Ma et al, 2012a(Ma et al, , 2012bZhang et al, 2015) and…”
Section: Provenancesupporting
confidence: 91%
See 3 more Smart Citations
“…Ma adakites (zircon ε Hf (t) = -0.8~+2.7; Mao et al, 2010b) and 397 ± 3 Ma K-feldspar granite By contrast, Precambrian detrital zircons in this study correspond well with those previously reported Precambrian detrital zircons (Ma et al, 2012a(Ma et al, , 2012bZhang et al, 2015) and…”
Section: Provenancesupporting
confidence: 91%
“…8 and 9;Zhang et al, 2015). A recent detrital zircon study of sedimentary rocks from the southern margin of the Junggar Basin has also revealed that the detrital zircons were derived dominantly from the southern Chinese Tianshan since the initiation of the basin in the Late Carboniferous (Yang et al, 2013).…”
Section: Provenancementioning
confidence: 99%
See 2 more Smart Citations
“…This study is mainly focused on the western part of the Tianshan orogenic collage, since the eastern Tianshan has probably undergone a discrete Paleozoic evolution (Y.G. Han et al, , 2016aZhang et al, 2016).…”
Section: Geological Settingmentioning
confidence: 99%